A Comparison Between Low-Level Laser Therapy and Intra-articular Ozone Injection in Knee Osteoarthritis Treatment: A Randomized Clinical Trial: Low-Level Laser or Intra-articular Ozone in Knee Osteoarthritis - Fakhari, Solmaz; Pishghahi, Alireza; Pourfathi, Hojjat; Farzin, Haleh; Bilehjani, Eissa (Journal of Lasers in Medical Sciences, 2021)
Introduction: Knee osteoarthritis is a common degenerative joint disease, causing deformity, pain and a limited joint range of motion. Modification of the lifestyle and an exercise training program is the cornerstone of treatment. Alternative therapies such as laser or ozone are commonly used, but there is not any comparative study of low-level laser therapy versus ozone therapy. The aim of the study was to compare the efficacy and safety of the LLLT versus ozone in patients with KOA. Methods: In this single-blinded randomized clinical trial, 60 patients with KOA were assigned to LLLT or ozone groups (n=30). The First basic pain severity, the Western Ontario and McMaster Universities Arthritis Index (WOMAC) score, and physical function were determined. Then in the LLLT group, the patients were provided with 12 sessions of LLLT. In the ozone group, 6 sessions of intra-articular injection of ozone were organized (in each session a mixture of 10 mL of bupivacaine 0.25% with 15 mL of ozone 30 μg/mL). In the middle and at the end of the intervention period, we reassessed the joint pain and physical function and the degree of improvement compared between the two groups. Result: In the middle and at end of the treatment period in both groups, the joint pain decreased significantly. The same as pain, the self-administrated WOMAC score and the range of joint motion improved significantly in both groups. All of these variables exposed more improvement in the ozone group patients. Conclusion: The study showed that both LLLT and ozone are acceptable non-invasive methods in the non-surgical treatment of KOA. Compared to LLLT, the ozone was more effective. These methods must be considered in any patient who is not suitable for surgical interventions or does not experience enough improvement in symptoms following long periods of common exercise training programs. DOI:10.34172/jlms.2021.44